Up and Down Nasi Sek di Pariaman (1980-2019) - Nurfita Falmia; Siti Fatimah (Jurusan Sejarah FIS UNP, 2026)
This study examines the of the development of Nasi Sek as a traditional culinary specialty of the coastal communities of Pariaman between 1980 and 2019. The study aims to explain the background to the emergence of Nasi Sek, its development as a regional culinary specialty, and the factors that led to its decline by the end of the study period. The study employed a historical method with a descriptive-analytical approach, encompassing heuristics, source criticism, interpretation, and historiography. Data were obtained through field observations and interviews with Nasi Sek vendors, fishermen, coastal communities, and tourists, supported by documentation and various relevant literature sources.The results indicate that Nasi Sek began to develop in the coastal communities of Pariaman around the 1980s as a food suitable for fishermen due to its accessibility, convenience, and affordability. Along with the development of the tourism sector, particularly in the Gandoriah Beach area, Nasi Sek experienced significant growth between 1990 and 2009. This development was evident in the increasing number of vendors, the increasing variety of chili sauces and side dishes, and the increasing recognition of Nasi Sek among tourists as a Pariaman culinary specialty. However, between 2017 and 2019, Nasi Sek's presence showed a downward trend, marked by a decrease in the number of stalls and declining consumer interest. This situation was influenced by competition from modern culinary delights, changes in consumer consumption patterns, rising raw material prices, and a pricing system influenced by the Bangkuang culture. Despite facing various challenges, Nasi Sek continues to maintain its presence as a culinary heritage with economic, social, and cultural value for the coastal communities of Pariaman.